Comprehensive income and stock price: the case of the energy industry - Poniatowski, Przemysław (Wynik całkowity a cena akcji na przykładzie spółek z branży energetycznej, 2021)
Financial results are the main source of information for investors on the stock market. The International Accounting Standards Board has been changing the basic rules regarding a shift from net income to comprehensive income as the main picture of the financial performance of a business. Up to now net income has been frequently researched for usefulness in financial analysis and its association with market returns and the stock price. The results of previous research are not consistent. Comprehensive income has been rarely analysed in this aspect. The article examines the relation between comprehensive income and stock price of the energy industry companies listed on the Warsaw Stock Exchange in the period 2010-2019. The author showed the theoretical and legal aspects of comprehensive income and analysed its influence on the stock price and market returns, using a quantitative approach.
Financial Sciences. Nauki o Finansach, 2021, vol. 26, no. 1, s. 73-85
Keywords: comprehensive income; stock price; statement of comprehensive income; clean surplus; wynik całkowity; dochód całkowity; cena akcji; sprawozdanie z całkowitych dochodów